Whole‐body and adipose tissue metabolic phenotype in cancer patients. Issue 2 (28th January 2022) - Anderson, Lindsey J.; Lee, Jonathan; Anderson, Barbara; Lee, Benjamin; Migula, Dorota; Sauer, Adam; Chong, Nicole; Liu, Haiming; Wu, Peter C.; Dash, Atreya; Li, Yi‐Ping; Garcia, Jose M.
Abstract: Background: Altered adipose tissue (AT) metabolism in cancer‐associated weight loss via inflammation, lipolysis, and white adipose tissue (WAT) browning is primarily implicated from rodent models; their contribution to AT wasting in cancer patients is unclear. Methods: Energy expenditure (EE), plasma, and abdominal subcutaneous WAT were obtained from men (aged 65 ± 8 years) with cancer, with (CWL, n = 27) or without (CWS, n = 47) weight loss, and weight‐stable non‐cancer patients (CON, n = 26). Clinical images were assessed for adipose and muscle area while plasma and WAT were assessed for inflammatory, lipolytic, and browning markers. Results: CWL displayed smaller subcutaneous AT (SAT; P = 0.05) and visceral AT (VAT; P = 0.034) than CWS, and displayed higher circulating interleukin (IL)‐6 ( P = 0.01) and WAT transcript levels of IL‐6 ( P = 0.029), IL‐1β ( P = 0.042), adipose triglyceride lipase ( P = 0.026), and browning markers ( Dio2, P = 0.03; PGC‐1a, P = 0.016) than CWS and CON. There was no difference across groups in absolute REE ( P = 0.061), %predicted REE ( P = 0.18), circulating free fatty acids (FFA, P = 0.13) or parathyroid hormone‐related peptide (PTHrP; P = 0.88), or WAT protein expression of inflammation (IL‐6, P = 0.51; IL‐1β, P = 0.29; monocyte chemoattractant protein‐1, P = 0.23) or WAT protein or gene expression of browning (uncoupling protein‐1, UCP‐1; P = 0.13, UCP‐1, P = 0.14). In patients with cancer, FFA was moderately correlated with WAT hormone‐sensitive lipase transcript ( r = 0.38, P = 0.018, n = 39); circulating cytokines were not correlated with expression of WAT inflammatory markers and circulating PTHrP was not correlated with expression of WAT browning markers. In multivariate regression using cancer patients only, body mass index (BMI) directly predicted SAT ( N = 25, R 2 = 0.72, P < 0.001), VAT ( N = 28, R 2 = 0.64, P < 0.001), and absolute REE ( N = 22, R 2 = 0.43, P = 0.001), while BMI and WAT UCP‐1 protein were indirectly associated with %predicted REE ( N = 22, R 2 = 0.45, P = 0.02), and FFA was indirectly associated with RQ ( N = 22, R 2 = 0.52, P < 0.001). Conclusions: Cancer‐related weight loss was associated with elevated circulating IL‐6 and elevations in some WAT inflammatory, lipolytic and browning marker transcripts. BMI, not weight loss, was associated with increased energy expenditure. The contribution of inflammation and lipolysis, and lack thereof for WAT browning, will need to be clarified in other tumour types to increase generalizability. Future studies should consider variability in fat mass when exploring the relationship between cancer and adipose metabolism and should observe the trajectory of lipolysis and energy expenditure over time to establish the clinical significance of these associations and to inform more mechanistic interpretation of causation.